2021
DOI: 10.1101/2021.08.05.21261677
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phenotyping of acute and persistent COVID-19 features in the outpatient setting: exploratory analysis of an international cross-sectional online survey

Abstract: BACKGROUNDLong COVID, defined as presence of COVID-19 related symptoms 28 days or more after the onset of acute SARS-CoV-2 infection, is an emerging challenge to healthcare systems. The objective of this study was to phenotype recovery trajectories of non-hospitalized COVID-19 individuals.METHODSWe performed an international, multi-center, exploratory online survey study on demographics, comorbidities, COVID-19 symptoms and recovery status of non-hospitalized SARS-CoV-2 infected adults (Austria: n=1157), and I… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“… Radar chart illustrating the prevalence of the specific long COVID symptoms in the cohort studies with study number indicated on the circle circumference [ 15 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , ...…”
Section: Resultsmentioning
confidence: 99%
“… Radar chart illustrating the prevalence of the specific long COVID symptoms in the cohort studies with study number indicated on the circle circumference [ 15 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , ...…”
Section: Resultsmentioning
confidence: 99%
“…COVID‐19 is characterized by a heterogeneous clinical manifestation and divergent courses of the disease [2]. This ranges from asymptomatic infection, to ambulatory disease with wide‐ranged flu‐like complaints, up to severe respiratory or multiorgan failure, requiring hospitalization and treatment at intensive care unit [2–4]. Especially in the latter cases, an excessive overstimulation of the immune system, likewise driven by an impaired immune control of viral replication leads to a “cytokine release syndrome” with subsequent organ damage [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical phenotypes will be categorised from milder to more severe disease presentation and potential predicting factors (measured at presentation) will be identified using generalized linear mixed models. Generalised mixed models will be also used to assess the associations between the duration and severity of signs/symptoms of COVID-19 disease and viral loads, anti-SARS-CoV-2 antibody kinetics 20 and change in laboratory parameters and cytokines, after adjusting for age and gender. The likelihood ratio test will assess statistical significance of the estimates at the 5% level.…”
Section: Acute Diseasementioning
confidence: 99%
“…The WHO clinical progression scale [19] classifies mild disease into asymptomatic and into two broad symptomatic strata. However, COVID-19 patients have diverse clinical presentations encompassing the number and duration of symptoms [20] as well as different alterations of laboratory parameters. Some of these clinical phenotypes could be linked to evolution to severe disease and/or to the development of long-term sequelae [21].…”
Section: Introductionmentioning
confidence: 99%